2020
DOI: 10.1200/jco.19.01963
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Cost of Cancer Care: Beyond Drugs

Abstract: Author affiliations and support information (if applicable) appear at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…With rising expenditures on cancer care outpacing other sectors of the US health system, 1 , 2 , 3 national attention has focused on identifying and promoting high-value cancer hospitals, ie, those that consistently deliver excellent outcomes at relatively low cost. 4 National Cancer Institute (NCI)–designated cancer centers (hereafter NCI centers) are academic hospitals recognized for their scientific and research leadership, training and education programs, and clinical expertise in cancer care.…”
Section: Introductionmentioning
confidence: 99%
“…With rising expenditures on cancer care outpacing other sectors of the US health system, 1 , 2 , 3 national attention has focused on identifying and promoting high-value cancer hospitals, ie, those that consistently deliver excellent outcomes at relatively low cost. 4 National Cancer Institute (NCI)–designated cancer centers (hereafter NCI centers) are academic hospitals recognized for their scientific and research leadership, training and education programs, and clinical expertise in cancer care.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of cancer as a global health problem has increased considerably in the last 3 decades, climbing from the sixth to the second worldwide cause for disability‐adjusted life‐years from 1990 to 2017 1 . Its burden is reflected in costs for healthcare systems such as in the United States, where they have increased at a higher rate than any other healthcare sector, from $27 billion in 1990 to an overall expenditure of $137 billion in 2017 2,3 . In Europe, where studies have consistently reported that spending on cancer care is associated with better outcomes, it grew from €52 billion in 1995 to €103 billion in 2018 4 …”
Section: Introductionmentioning
confidence: 99%
“…1 Additionally, although cancer mortality has declined, the cost of diagnosing and managing cancer continues to increase and is estimated to account for 7% of all healthcare spending, outpacing all other sectors of healthcare. 3 These changes in cancer trends are leading to an urgency to identify and reverse the increase in incidence of certain types of cancer and reduce overall costs of managing an ever-growing population of cancer survivors. With the decline in tobacco use, dietary factors and obesity are becoming one of the leading causes of cancer.…”
mentioning
confidence: 99%